The Palgrave Handbook of Prison Ethnography - Drake, Deborah H. (Palgrave Studies in Prisons and Penology Ser., 2015)
This handbook presents a rich collection of chapters that focus on the method and experience of in-depth, ethnographic research in prisons. It provides an authoritative and diverse array of international perspectives that collectively demonstrate the social and political dimensions of the use and experience of imprisonment worldwide.